Factors associated with physical activity policy and practice implementation in British Columbia’s childcare settings: a longitudinal study - Tugault-Lafleur, Claire N.; Naylor, Patti-Jean; Carson, Valerie; Faulkner, Guy; Lau, Erica Y.; Wolfenden, Luke; Mâsse, Louise C. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background In 2016–17, the government of British Columbia (BC) enacted a mandatory policy outlining Active Play Standards (AP Standards) alongside a capacity building initiative (Appetite to Play) focused on implementing policies and practices to support physical activity in childcare centres. We aimed to identify factors at the provider and organizational levels as well as attributes of the Standards hypothesized to influence implementation (i.e., changes in policies and practices). Methods We conducted surveys before (2016–2017) and after (2018–2019) enforcement of the AP Standards among 146 group childcare centres across BC. The 2018–19 surveys measured theoretically based constructs associated with implementation of policies and practices (9 childcare- and 8 provider- level characteristics as well as 4 attributes of the licensing standards). Characteristics that were associated in simple regression models were entered in multivariable regression models to identify factors associated with policy and practice changes related to fundamental movement skills (FMS), screen time, total amount of active play (AP) and total amount of outdoor AP from baseline to follow-up. Results In multivariable analyses, higher staff capacity (OR = 2.1, 95% 1.2, 3.7) and perceived flexibility of the standards (OR: 3.3, 95% 1.5, 7.1) were associated with higher odds of a policy change related to FMS. Higher staff commitment to the AP standards was associated with a higher odds of policy changes related to screen time (OR = 1.6, 95% CI: 1.1, 2.4) and amount of AP (OR: 1.5, 95% 1.0, 2.3). Higher institutionalization of PA policies was associated with a higher odds of policy changes related to the amount of AP (OR: 5.4, 95% CI: 1.5, 20). Higher self-efficacy was associated with a higher odds of policy changes related to outdoor AP (OR = 2.9, 95% 1.1, 7.8). Appetite to Play training was a positively associated with practice changes related to FMS (β = 0.5, 95% CI: 0.1, 0.9). Conclusions A hierarchy of theoretically defined factors influenced childcare providers’ implementation of the AP Standards in BC. Future research should test the feasibility of modifying these factors to improve the implementation of PA policy and practice interventions in this setting.